Conjunctival Microbiome-Host Responses Are Associated With Impaired Epithelial Cell Health in Both Early and Late Stages of Trachoma - Pickering, Harry; Palmer, Christine D.; Houghton, Joanna; Makalo, Pateh; Joof, Hassan; Derrick, Tamsyn; Goncalves, Adriana; Mabey, David C. W.; Bailey, Robin L.; Burton, Matthew J.; Roberts, Chrissy H.; Burr, Sarah E.; et al. (Frontiers in Cellular and Infection Microbiology, 2019)
Background Trachoma, a neglected tropical disease, is the leading infectious cause of blindness and visual impairment worldwide. Host responses to ocular chlamydial infection resulting in chronic inflammation and expansion of non-chlamydial bacteria are hypothesised risk factors for development of active trachoma and conjunctival scarring Methods Ocular swabs from trachoma endemic populations in The Gambia were selected from archived samples for 16S sequencing and host conjunctival gene expression. We recruited children with active trachoma and adults with conjunctival scarring, alongside corresponding matched controls. Findings In children, active trachoma was not associated with significant changes in the ocular microbiome. Haemophilus enrichment was associated with antimicrobial responses but not linked to active trachoma. Adults with scarring trachoma had a reduced ocular bacterial diversity compared to controls, with increased relative abundance of Corynebacterium. Increased abundance of Corynebacterium in scarring disease was associated with innate immune responses to the microbiota, dominated by altered mucin expression and increased matrix adhesion. Interpretation In the absence of current Chlamydia trachomatis infection, changes in the ocular microbiome associate with differential expression of antimicrobial and inflammatory genes that impair epithelial cell health. In scarring trachoma, expansion of ‘non-pathogenic’ bacteria such as Corynebacterium and innate responses are coincident, warranting further investigation of this relationship. Comparisons between active and scarring trachoma supported the relative absence of interferon-gamma responses in scarring, whilst highlighting a common suppression of re-epithelialisation with altered epithelial and bacterial adhesion, likely contributing to development of scarring pathology.